Surgical patient safety: evaluation of perioperative checklist implementation - Dos Santos Silva Ribeiro, Célia Aparecida (2022)
Objective: To describe the adherence to the completion of the safe surgery checklist and its respective items by nursing professionals in the operating room of a public hospital in the DF. Method: This is a nevaluation study that a ims to support decision-making to improve the care provided to surgical patients. Results: Showed the adhesion of 253.5 out of a total of 270 points, 10 points attributed to each item in the Judgment Matrix check. The demarcation of the laterality of the surgical site, checked in the Sing out, was considered of lesser relevance by the interviewees, this being the surgeon's attribution. Conclusion: The successful adherence to the Perioperative checklist can be attributed to on going education alawareness interventions, lectures and continuing education on the subject.